World market opportunitues for Nigerian vegetable oil products: report to the Ministry of Commerce and Industry, Federal Republic of Nigeria (Cambridge Arthur D. Little Inc, 1964)
This report is not simply a review of the volume of data available on world markets for oils and fats. It presents the understanding and measurement of the complex interrelationships of supply and demand which determine the existence of market opportunity
osc 06/03/2019
Loans
Keywords: International trade; Nigeria